DAMPAK GAME ONLINE: MOBILE LEGENDS PADA MAHASISWA - Defio Mario Ratu; Melky Pangemanan (VitaMedica : Jurnal Rumpun Kesehatan Umum, 2024)
Online gaming has become an integral part of the lives of many college students around the world. This phenomenon has a variety of impacts, both positive and negative. Playing online games is an activity that is carried out with the aim of obtaining pleasure without considering what will happen from the activity. This study aims to determine the impact of the online game Mobile Legends: Bang Bang on students of the Islamic Communication and Broadcasting study program at the Bone State Islamic Religious Institute. This research uses field research and the type of research is qualitative research. Data processing in this study is carried out by processing and analyzing data qualitatively. Qualitative data processing and analysis are carried out through data reduction, data presentation, verification and conclusion drawn. The results of the study show that the impact of online games consists of two, namely negative impact and positive impact. The positive impacts of online games are skill development, hand-eye coordination, social skills and collaboration, language development, and a source of entertainment and relaxation. Negative impacts are dependence and addiction, physical health, social isolation, financial impact, and stress levels.